The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1063/1.1467338
|View full text |Cite
|
Sign up to set email alerts
|

Variational principles for describing chemical reactions: Condensed reactivity indices

Abstract: Two recent papers [P. W. Ayers and R. G. Parr, J. Am. Chem. Soc. 122, 2010 (2000); 123, 2007 (2001)] have shown how variational principles for the energy may be used to derive and elucidate the significance of the chemical reactivity indices of density-functional theory. Here, similar ideas are applied, yielding a systematic, mathematically rigorous, and physically sound approach to condensed reactivity indices. First, we use the variational principle for the energy to derive an expression for the condensed Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
177
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(191 citation statements)
references
References 31 publications
10
177
0
3
Order By: Relevance
“…The reason why Hirshfeld charges are so small can be related to the work by Ayers who has shown that the Hirshfeld weighting factor is such that it makes the AIM as similar as possible to the isolated atom. 17,28 It is therefore not surprising that also the atomic properties of the AIM are as similar as possible to that of the isolated atom. One of these properties is the atomic population.…”
Section: ͑1͒mentioning
confidence: 99%
“…The reason why Hirshfeld charges are so small can be related to the work by Ayers who has shown that the Hirshfeld weighting factor is such that it makes the AIM as similar as possible to the isolated atom. 17,28 It is therefore not surprising that also the atomic properties of the AIM are as similar as possible to that of the isolated atom. One of these properties is the atomic population.…”
Section: ͑1͒mentioning
confidence: 99%
“…[16][17][18]31,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Las ecuaciones básicas de la DFT, se obtienen a través de la minimización del funcional de energía de la densidad electrónica, E[ρ] con la restricción que el número de electrones (N) permanezca constante, conduciendo a la expresión mostrada en la Ecuación 1:…”
Section: Fundamentos Teóricosunclassified
“…Descriptores globales y locales calculados al nivel mPW1PW/LANL2DZ* para los derivados propuestos acumulación o disminución de la densidad electrónica sobre un sitio particular de la molécula, aun cuando el número de electrones aumente o disminuya en uno. 75 Por otro lado, Ayres, 43 recientemente relacionó el comportamiento anteriormente expuesto con la reducción u oxidación de centros atómicos en determinada molécula. Estos valores negativos constituyen un verdadero rompecabezas a la hora de analizar los datos, así que, dentro de las estrategias para superar la complejidad asociada a dichos valores negativos para FF, Kolandaivel y colaboradores, 32 propusieron el descriptor atómico (sf ) k α , con el cual obtuvieron resultados confiables para las tendencias de reactividad de un grupo de moléculas seleccionadas.…”
Section: Cis-dicloro[no-valina]platino(ii)unclassified
“…(The factor C LCC is omitted in our illustrative example tests as it is irrelevant at comparisons). Note that (C LCC ) −1 equals to one when the FF is not negative, but it is larger than one (even two) when FF is negative in some regions as in cases of redox-induced electron transfer [38,39]. This Δ LCC is the last indicator for testing the quality of functionals, proposed in this work.…”
Section: Theoretical Backgroundmentioning
confidence: 99%